Scaling Up Handwashing Behavior : Findings from the Impact Evaluation Baseline Survey in Vietnam - Chase, Claire (World Bank, Washington, DC, 2014)
The goal of global scaling up handwashing is to reduce the risk of diarrhea and therefore increase household productivity by stimulating and sustaining the behavior of handwashing with soap at critical times in the lives of 5.4 million people in Peru, Senegal, Tanzania, and Vietnam, where the project has been implemented to date. The structure of this report proceeds as follows: In chapter one author provide an overview of the global scaling up handwashing and global scaling up rural sanitation projects, as well as background on the handwashing project in Vietnam. Chapter two details the methodology that underlies the impact evaluation, and provides details on the sampling design, sample selection, and field work protocols. The baseline findings for general household characteristics, handwashing behavior, child health, and child growth are presented in depth in chapter three. In chapter four authors conclude with a summary of the next steps of the impact evaluation study.